Imperfect Capital Mobility in an Open Economy Model of Capital Accumulation - Klyuev, Vladimir (Washington, D.C. : International Monetary Fund, 2004)
This paper introduces a tractable capital market friction mechanism that allows a break of the parity between domestic and external interest rates and generates a gradual evolution of capital stock and other macroeconomic variables-in contrast to the instantaneous convergence found in models with interest rate parity. The friction, derived from explicit microfoundations, is such that the cost of new loans is an increasing function of net borrowing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet